2015
DOI: 10.2340/00015555-1965
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Skin Pain: Instrumental and Biological Evaluations

Abstract: The prevalence of skin pain and the molecular mechanisms responsible for pain in psoriasis remain unclear. This study assessed skin pain in 163 patients (98 males, 65 females, range 18-81 years) with plaque psoriasis, evaluating: the subjective/objective features of this symptom compared with clinical severity of the disease; and the role of interleukin (IL)-33, (involved in both psoriasis and pain pathogenesis), in psoriasis-related pain. Clinical measures used were a questionnaire, plaque Physician Global As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 31 publications
6
52
0
1
Order By: Relevance
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 80%
“…These cells share a common intracellular domain (TIR domain) that may, through MyD88, initiate a signaling cascade, leading to NF-κB translocation (23). IL-33 has been found to be expressed at elevated levels in affected psoriatic skin, compared with healthy skin, and it has also been proposed to represent a novel marker of psoriasis, relative to other inflammatory skin disorders (25)(26)(27)(28). Balato et al (25) recently demonstrated that inflammatory cytokines, such as TNF-α, induce the secretion of IL-33 from immortalized keratinocytes (24) and support the hypothesis that IL-33 has an important role in the effect of anti-TNF therapy on psoriatic skin (25,29).…”
Section: Introductionmentioning
confidence: 99%
“…A tendency of reduced pressure pain thresholds in unlesioned skin of patients with PsV compared to controls was also found in another study. 3 One explanation for our results is polyneuropathy, possibly resulting from the higher risk for (pre-) diabetes 7 and metabolic syndrome in patients with PsV, 8 conditions known to cause changes in somatosensory function. In line with that, our patient group reported significant more signs of paraesthesia.…”
mentioning
confidence: 84%
“…Typical inflammation-induced algogenic mediators include prostaglandins, serotonin, and bradykinin; in addition, leukotrienes and interleukins display proinflammatory effects. A recent study by Patruno et al [3] Pain associated with skin diseases is mostly nociceptive pain, which can be triggered by mechanical, thermal, and/ or chemical noxious stimuli. Neuropathic pain is caused by damage to the peripheral or central nervous system.…”
Section: Pain Transduction/transmission and Pain Modulationmentioning
confidence: 99%